RESTORATION OF LONG-FALLOW LANDS IN THE CONDITIONS OF THE INCREASED MOISTURE - N. I. Dzhabborov; A. V. Dobrinov (Сельскохозяйственные машины и технологии, 2015)
The agricultural lands, which are not used in a crop rotation, grow over with weed vegetation forming a thick sod cover. The greatest damage is caused by overgrowing of the farmland a bush and a half-grown forest. Especially it is shown in the conditions of the increased moisture. Technologies and technical means for restoration of not cultivated lands should correspond to conditions of zone specifics. The volume and rates of introduction of the long-fallow lands depend on technical equipment of the agricultural enterprises. The combined soil-cultivating unit Leader-2.5Н and the modular ring harrows Lider-BKM-6 were tested. They intended for introduction of fallow lands. These machines are worked out by JSC Sibirskiy Agropromyshlennyy Dom (Novosibirsk). Hardness of the soil changes depending on processing depth. In the 0-10 cm layer it decreases from 13 to 8.2-8.3 kg/sq•cm, in a layer of 10-20 cm - from 18.7 to 9.7-12.8 kg/cc, at a depth of 20-30 cm - from 26.1 to 15.7-24.1 kg/sq•cm. It was showed that energy consumption on recovery of 1 hа of wetlands make 1932.24 MJ that is equivalent 45.25 kg of diesel fuel.